Beneath the hairy look: the hidden reproductive diversity of the Gibsmithia hawaiiensis complex (Dumontiaceae, Rhodophyta). Issue 6 (9th November 2017) - Gabriel, Daniela; Draisma, Stefano G.A.; Schmidt, William E.; Schils, Tom; Sauvage, Thomas; Maridakis, Clio; Gurgel, C. Frederico D.; Harris, D. James; Fredericq, Suzanne
Abstract : The tropical alga previously recognized as Gibsmithia hawaiiensis (Dumontiaceae, Rhodophyta) was recently suggested to represent a complex of species distributed throughout the Indo‐Pacific Ocean and characterized by a peculiar combination of hairy (pilose) gelatinous lobes growing on cartilaginous stalks. Phylogenetic reconstructions based on three genetic markers are presented here with the inclusion of new samples. Further diversity is reported within the complex, with nine lineages spread in four major phylogenetic groups. The threshold between intra‐ and interspecific relationships was assessed by species delimitation methods, which indicate the existence of 8–10 putative species in the complex. Two species belonging to the G. hawaiiensis complex are described here: Gibsmithia malayensis sp. nov. from the Coral Triangle and Gibsmithia indopacifica sp. nov., widely distributed in the Central and Eastern Indo‐Pacific. Morphological differences in the vegetative and reproductive structures of the newly described species are provided and compared to the previously described species of the complex. Additional lineages represent putative species, which await further investigation to clarify their taxonomic status. Gibsmithia hawaiiensis sensu stricto is confirmed to be endemic to the Hawaiian Islands, and Gibsmithia eilatensis is apparently confined to the Red Sea, with an expanded distribution in the region. New records of the G. hawaiiensis complex are reported from Egypt, Saudi Arabia, Indonesia, Philippines, and the Federated States of Micronesia, indicating that the complex is more broadly distributed than previously considered. The isolated position of Gibsmithia within the Dumontiaceae is corroborated by molecular data.